LOS COMUNISTAS BOLIVIANOS Y LA KOMINTERN: UNA HISTORIA DE DESENCUENTROS - Schelchkov, Andrey; Stefanoni, Pablo (Historia mexicana, 2023)
The formation of the first communist party in Bolivia, in the 1930s, went against the grain of the intentions of the Communist International, represented by its South American Secretariat (SSA), to establish a party in the Andean country aligned with the established conditions. during the “Third Period”, including the “Bolshevization” of its ideological and organizational structures. The political initiative and heterodox programmatic ideas of the Bolivian communists, their willingness to discuss among equals, without accepting the dictates of the Comintern as a dogma, and their own political inexperience added to the scarcity of material and intellectual means, did not take long, without However, in making the first efforts to establish a party of their own fail. This article analyzes the ideas and programs of the proto-parties created in those years, especially the Confederation of Workers' Republics of the Pacific (crop), the trinational communist party project (Bolivian-Peruvian-Chilean), developed by José Antonio Arze.